English language teachers’ experiences with the first transition to online education during COVID-19 - K. Váradi (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
Teaching English as a foreign language is important in the 21st century. However, as a result of the sudden outbreak of the COVID-19 pandemic and the consequential quarantine measures in March 2020, the education process had to be reorganised from the traditional face-to-face method to the online space within a few days. English teachers had to face previously not experienced problems all over the world. The purpose of this study was to shed light on the main obstacles that emerged during the first transition to digital education in the spring of 2020. With the help of semi-structured interviews, sixteen English language teachers were asked from various Transcarpathian secondary and higher education institutions about their experiences with online education and the useful practices which helped them overcome the most serious problems. Based on the results, the personal contact between teachers and learners was important in the development of speaking skills in a foreign language. Although online education was rather convenient and advantageous in terms of developing listening, reading, or writing skills, distance education was not as effective as the traditional face-to-face context. Several problems emerged in connection with the demotivation of students, the overload of both teachers and learners, the lack of the Internet connection or digital equipment, and the unpreparedness of teachers and educational institutions. The practical significance of this study is that it gives possible solutions to these issues and hindrances, thus teaching English in the online space could be more effective